Eiffel et la météorologie - Peter, Martin (Comptes Rendus. Mécanique, 2023)
The wind has always been a major concern for Gustave Eiffel due to its effects on the large metal constructions he made. “The wind, my enemy”, he said. Eiffel expresses through his speeches his desire to put science at the service of technology. Meteorology must help the aviator, the peasant or the sailor. It is for men that Gustave works. He therefore recommends simplifying practices so that the results are accessible to all. So the meteorology must give usable information immediately.